Arabic education in University of Ilorin, Nigeria: a review - Salisu, Alfa Muhammed; Dollah, Nafi@Hanafi; Zakaria, Abd Wahab (Contemporary Research Center Australia, 2014)
Arabic Education has flourished and passed different stages and media in Nigeria over time. It has as such played significant role in spreading Islamic civilization outside the Arabian Peninsula. Historical records confirmed that for about three centuries between 17th and 19th centuries Arabic documents remained the only source of information for European writers on western and central Sudan. It was also a means of communication and language of instruction in different stages in Nigeria over the years. Meanwhile, the language is facing a lot of challenges in Nigerian Universities, ranging from Government policies on language education, social, pedagogical, etc. that may impede its aims and objectives. Some of these challenges came as a result of the educational policies. This paper attempts to discuss the role of Arabic language in the Islamic civilization in Nigeria and the current status of Arabic education in Nigerian Universities with special reference to the Nigerian Language policies and implementation in relation to the pedagogical situation of Arabic language in University of Ilorin, Nigeria.